HUBUNGAN POLA ASUH ORANG TUA DENGAN PERILAKU HIDUP BERSIH DAN SEHAT ANAK DI PONDOK PESANTREN AL-HAMID - Dewanto, Saskia; Zulfa, Vania; Faesal, M (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
This study aims to determine the relationship of parenting parents with the behavior of clean and healthy life of children in Pondok pesantren Al-Hamid. This study is a quantitative research using motode survey with correlational approach data collection is done by distributing non-test questionnaires directly to students with random sampling data collection techniques with the number of 165 students representing students in Pondok Pesantren Al-Hamid. The collection of research data began in December 2021 until January 2022. Prerequisite test data analysis technique using KolmogorovSmirnov normality test and correlation test using Pearson product Moment Correlation, and correlation significance test. The results of this study is that there is a relationship between parenting parents with the behavior of clean and healthy life of children in boarding schools by 0.303. This study shows that there is a relationship between parenting parents with the behavior of clean and healthy life of children in Pondok Pesantren Al-Hamid.